REGULATING PRIVATE SECURITY COMPANIES (PSCs) AND PRIVATE MILITARY COMPANIES (PMCs) UNDER THE LAW OF TIMORLESTE - Salvador Soares; David Price (Fakultas Hukum Universitas Gadjah Mada, 2014)
Use of Private Security Companies (PSCs) and Private Military Companies (PMCs) in conflict and post-conflict countries has been the subject of ongoing critical discussion among scholars and media for many years. This paper assesses the legal status and responsibilities of PSCs and PMCs, and their operation in Timor-Leste where they are not properly regulated. It examines key legal issues, such as their definition and roles, scope and limits of operations, approved and prohibited activities, accountability, and monitoring. The paper also examines the impact of PSCs and PMCs on Timor-Leste law and society and offers astatutory framework for their management and regulation. Implementasi Private Security Companies (PSCs) dan Private Military Companies (PMCs) dalam negara yang sedang berkonflik dan pasca berkonflik telah menjadi subjek pembahasan penting diantara akademisi dan media massa selama bertahun-tahun. Penulisan ini akan menilai status hukum dan kewajiban PSCs dan PMCs, dan pelaksanaan kerja kedua lembaga tersebut di Timor-Leste dimana belum ada pengaturan yang mumpuni. Penulisan ini menganalisa isu-isu krusial mengenai beberapa pengaturan, seperti definisi dan peran, batasan dan ruang lingkup kerja, aktivitas yang diperbolehkan dan yang dilarang, akuntabilitas, serta pengawasan. Penulisan ini juga menganalisa implikasi dari PSCs dan PMCs di tatanan hukum dan masyarakat Timor-Leste, serta menawarkan sebuah kerangka undang-undang untuk manajerial dan pengaturan kedua lembaga tersebut.